The application of metaverse in mental health - Wang, Yue; Duan, Boshi; Chen, Xi; Song, Yuxuan; Liu, Xin (Frontiers in Public Health, 2025)
Rapid technological progress is reshaping human existence globally. The metaverse, a 3D digital realm merging virtual reality (VR) with physical space, exemplifies this fusion. Users can replicate and customize real-world elements within this immersive environment. Over the past decade, VR, augmented reality (AR), and mixed reality (MR) have become effective tools for addressing mental health conditions, offering solutions to the shortage of mental health professionals and limited access to care. However, extensive participation in 3D immersive gaming and social media can lead to insecurity, anxiety, depression, and addictive behaviors, particularly among young adults. This engagement may also impair attention spans, exacerbating symptoms in adolescents with attention deficit hyperactivity disorder. This research examines the impact of expanding metaverse applications on mental health, exploring both risks and benefits.